2005
DOI: 10.1016/j.jhsb.2005.05.003
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Absence of the Palmaris Longus – A Study in a Chinese Population and a Review of the Literature

Abstract: Most standard textbooks of hand surgery quote the prevalence of absence of palmaris longus at around 15%. However, this figure varies considerably in reports from different ethnic groups. We studied 329 Chinese men and women and found palmaris longus to be absent unilaterally in 3.3%, and bilaterally in 1.2%, with an overall prevalence of absence of 4.6%. There was no significant difference in its absence with regard to the body side or the sex. Our literature review revealed a low prevalence of absence in Asi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 12 publications
6
69
1
Order By: Relevance
“…This means that it is important to become aware of the prevalence of PLMT agenesis in the population being treated 19,20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…This means that it is important to become aware of the prevalence of PLMT agenesis in the population being treated 19,20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…Not only in terms of absence but also in variability of origin and insertion and morphology [1]. The PLM can be absent unilateral and bilateral in about 22.4% of human beings (Caucasians) with a range of 3.0%-63.9%, depending on the ethnic background of a population [2]. A great diversity is reported between different populations in the prevalence of absence of the PLM [3].…”
Section: Introductionmentioning
confidence: 99%
“…12.5% (75 subjects) showed unilateral absence and 18.75% (112 subjects) showed bilateral absence. [13] Ceyhan and Mavi [14] Studies among the Asian population showed that the incidence is 3.4% in Japanese, [15] 4.6% in Chinese, [16] and 0.6% in the Korean [17] respectively. Within Africa, studies have equally been conducted.…”
Section: Discussionmentioning
confidence: 99%